(untitled) (World Bulletin of Education and Learning, 2025)
The distribution of Ga and Sb atoms in silicon is observed and compound semiconductors are obtained by used to produce modern electronic elements are solar cells. Silicon is the only element on earth used in the production of electronic elements and solar cells.